Ecological Culture in the Theory and Practice of Environ-ment Cognition - Potapchuk, L. V. (Psychological Prospects Journal, 2011)
The theoretical approaches to the problem of ecological culture researches are represented in the theory and practice of environment cognition.
Keywords: personality culture ecological culture environment